Manajemen Lembaga Dakwah, Masalah dan Solusinya (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
Management of da’wah institutions plays an important role in Organizing da’wah activities so that they are carried out effectively, efficiently, and in accordance with organizational objectives. However, in practice, various challenges remain, including limited human resources, weak leadership, inadequate funding, suboptimal utilization of information technology, and weaknesses in Planning and evaluation systems. This study aims to analyze the concept of da’wah institution management, identify the challenges encountered, and formulate appropriate solutions. The study employed a qualitative approach using a library research method. Data were collected from books, scientific journals, and other relevant literature and analyzed using content analysis techniques. The findings indicate that the success of da’wah institution management is influenced by the implementation of management functions, the quality of human resources, leadership, financial management, the utilization of information technology, as well as monitoring and evaluation. Therefore, professional management grounded in Islamic values is essential to improve organizational governance and ensure that da’wah institutions perform their functions effectively and sustainably. To address these challenges, it is necessary to strengthen human resource competencies, reinforce leadership systems, develop strategic Planning, optimize digital technology, establish partnerships, and implement continuous cadre development. Based on the findings, it can be concluded that the application of professional management based on Islamic values enhances the governance quality of da’wah institutions, enabling them to adapt to changing times, gain public trust, and carry out their da’wah mission effectively and sustainably.